2021
DOI: 10.1002/cphc.202001051
|View full text |Cite
|
Sign up to set email alerts
|

Li8Si8, Li10Si9, and Li12Si10: Assemblies of Lithium‐Silicon Aromatic Units

Abstract: We report the global minima structures of Li8Si8, Li10Si9, and Li12Si10 systems, in which silicon moieties maintain structural and chemical bonding characteristics similar to those of their building blocks: the aromatic clusters Td−Li4Si4 and C2v−Li6Si5. Electron counting rules, chemical bonding analysis, and magnetic response properties verify the silicon unit‘s aromaticity persistence. This study demonstrates the feasibility of assembling silicon‐based nanostructures from aromatics clusters as building block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…4 shows the results of the AdNDP analysis. In the case of Li 6 Si 5 , we obtain a similar representation to the one previously reported, 52 five lone pairs, one on each Si, five Si–Si σ-bonds plus three delocalized π-bonds connecting the Si 5 ring, the latter consistent with the aromatic character of this cluster. 49,93,94 For the case of Li 10 Si 4 , AdNDP recovers six lone pairs (two on each of the three external silicon).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…4 shows the results of the AdNDP analysis. In the case of Li 6 Si 5 , we obtain a similar representation to the one previously reported, 52 five lone pairs, one on each Si, five Si–Si σ-bonds plus three delocalized π-bonds connecting the Si 5 ring, the latter consistent with the aromatic character of this cluster. 49,93,94 For the case of Li 10 Si 4 , AdNDP recovers six lone pairs (two on each of the three external silicon).…”
Section: Resultssupporting
confidence: 81%
“…Thus, for example, our group recently demonstrated that the global minima T d -Li 4 Si 4 and C 2v -Li 6 Si 5 consisting of Zintl Si 4 4− (tetrahedron) and Si 5 6− (pentagon) anions maintain their silicon motifs, almost unchanged, in the Li 8 Si 8 , Li 10 Si 9 , and Li 12 Si 10 combinations. 51,52 Furthermore, Li 6 Si 5 can be stacked to form a nanowire within a carbon nanotube. 53 These findings suggest that these small clusters could work as assembly blocks for CAMs, which is particularly interesting because these structural patterns have been identified in Li–Si materials.…”
Section: Introductionmentioning
confidence: 99%